Membership density and trade union power. (February 2017) - Crouch, Colin
Union membership has declined in almost all European and other advanced economies, though in many cases the membership that remains reflects overall changes in the gender and occupational structure of the economy. Meanwhile, in most countries unions' incorporation in governing institutions of the labour market has remained stable or risen. Union strength (membership density and incorporation) and to a lesser extent bargaining coordination correlate positively with core employee interests in the post-Keynesian economy: a combination of high employment and low inequality, and a balance between flexibility and security. The evidence suggests that unions' most important role today is as part of wider political forces, where the role of membership strength remains ambiguous.